Personality traits of handball goalkeepers - Fasold, F.; Inzenhofer, V.; Lingner, K.; Noël, B.; Klatt, S. (Journal of Human Sport & Exercise, 2020)
Goalkeeping in handball puts special demands on the athletes. Whereas on-court strain and conditional demands of the goalkeeper position are already intensively investigated, research on handball goalkeepers` personality traits is still lacking. In this study, the sport specific personality structure of male handball goalkeepers (N = 81) on competitive and leisure sport level was assessed for the first time, using a version of the BFI-10 adapted to the sport context. In comparison to the normal population, handball goalkeepers proved to be more conscientious, more neurotic, and less open for new experiences. A relation of the trait conscientiousness and the performance level became visible; goalkeepers on higher performance levels showed higher conscientiousness values. The current investigation presents a sport specific personality profile of handball goalkeepers for the first time, whereby derivations, for example, for the construction of talent diagnostic have to be seen more critical. The results of the current study provide the basis for further research which should, amongst others, especially focus on the comparison of the personality structure of goalkeepers and field players.